Low-Calorie Cookies Enhanced with Fish Oil-Based Nano-ingredients for Health-Conscious Consumers - Meral, Raciye; Kina, Erol; Ceylan, Zafer; Ceylan, Zafer (Amer Chemical Soc, 2024)
This study explored the effectiveness of fish oil (FO)-loaded nanoemulsions, averaging 197 nm in diameter, as fat substitutes in creating low-calorie cookies. The cookies' diameter, thickness, and spread ratio were measured, ranging from 46.33 to 57.15 mm, 6.45 to 7.51 mm, and 6.16 to 8.86, respectively. Notably, cookies containing nanoemulsions exhibited a significant increase in the spread ratio compared to the control. The control sample had the highest hardness value at 43.81 N, while the nanoemulsion group had the lowest at 26.98 N. The energy value, which was 508 kcal/100 g in the control group, decreased to 442 kcal/100 g in the group containing the nanoemulsion. The total n-3 fatty acid content in cookies rose from 0.46% in the control cookies to 3.90% in the cookies containing nanoemulsion. Sensory evaluations showed that cookies containing fish ol-loaded nanoemulsion received the highest scores, indicating that the fat reduction did not compromise the desired '' greasy '' sensation. This is especially noteworthy, as it showed that the fat content could be reduced by half without compromising the sensory quality. Utilizing FO-loaded nanoemulsions as a fat replacement in fat-reduced baked goods could provide valuable insights for other food products. The findings have significant implications for the food industry, suggesting that healthier, low-calorie baked goods can be developed without sacrificing physical quality and texture. This approach can cater to the growing market demand for health-conscious food options, potentially leading to new product innovations and enhanced nutritional profiles in a variety of food products.
Keywords: Oxidative Stability; Fat Replacer; Biscuits; Dough; Texture; Quality; Gluten; Flour; Sugar; Microstructure